Development and Evaluation of a Cognitive Conflict-Based Physics Learning Module in a Blended Learning Model - Gunawan, G.; Kosim, K.; Larasafitri, Martina Nur; Herayanti, Lovy (Journal of Applied Science, Engineering, Technology, and Education, 2024)
This study developed and evaluated the effectiveness of a cognitive conflict-based physics learning module within a blended learning environment. The module was designed to enhance high school students' critical thinking skills, which are essential for effective problem-solving and decision-making. The research employed the Research and Development (R&D) method with the 4-D model. The module was tested on two experimental classes, and student performance was assessed through a 5-item essay test and analysis of student worksheets. Results showed significant improvement in all aspects of critical thinking, particularly in basic clarification and inference. This improvement is attributed to the cognitive conflict approach, the blended learning model, and the engaging design of the module. The study concludes that this learning module is effective in fostering critical thinking skills and recommends further testing in other materials and contexts, additional module development, and teacher training.